Berakhirnya Sengketa Geprek Bensu - Amani, Fatimah Cahya; Japono, Saskia Salsabila; Tuassalamony, Adzra Ardelia (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Brand disputes are still one of the disputes in Indonesia due to a lack of awareness that brands only have legal certainty after they are registered. One of the brand disputes that occurred in Indonesia was the dispute between Ruben Onsu and Benny Sudjono over the I Am Geprek Bensu brand, which has been a long-standing dispute since 2018-2020. The research will explain the chronology of the brand dispute between Ruben Onsu and Benny Sudjono and how legal protection efforts will be provided to the parties involved in the dispute. The research uses normative legal methods with secondary data sources and the results are explained in the form of descriptive analysis through legal phenomena that occur in society. The results of the research explain that Ruben Onsu finally had to give up the Bensu brand and currently Geprek Bensu outlets are almost never found in Indonesia anymore and have become empty of buyers since this case occurred.